Encyclopedia of Guerrilla Warfare - Beckett, Ian F. W. frey50 (Santa Barbara, Calif. : ABC-CLIO, 1999)
An encyclopedia of articles examining guerrilla warfare throughout the world, focusing on military tactics utilized by minority groups within a state or indigenous population to oppose the ruling government or foreign occupying forces.
Keywords: Guerrilla warfare -- Encyclopedias; Guerrilla warfare -- Encyclopedias